Perancangan mesin perajang bawang serbaguna berpenggerak motor listrik dengan kapasitas 55 kg/jam - Riki Effendi; Muhammad Khumaidi (Jurnal POLIMESIN, 2018)
Abstract This study aims to create a versatile multipurpose machine design to support increasing production of Usaha Masyarakat Kecil Menengah (UMKM), especially in the business of onion slices that are ready to be fried. The design of this machine has several concepts with steps such as: requirement, problem analysis and specification, design of machine concept, technical analysis, modeling up to work drawing, tool making, assembling and testing. This machine uses electric motors with low power and the price is relatively cheap, so this machine is affordable for the community of UMKM. After doing research on slicing machine of onion by using onion slicer got maximum capacity of 55 kg per hour with 400 rpm slicing knife rotation and 1 mm slice thickness. Keywords: Designing, Chopping Machine, Red Onion, Slicer